Minor Myocardial Injury: An Early Post Intervention Complication - Afrin, Syeda Fahmida; Rahman, Md Hasanur; Millat, Md Asadul; Quarashi, Md Shafiul Alam; Begum, Asma; Begum, Meherunnesa (Delta Medical College Journal, 2017)
Percutaneous Coronary Intervention (PCI) is the most commonly performed invasive therapeutic cardiac procedure and plays an important role in the treatment of ischemic heart disease. Complications of Percutaneous Coronary Intervention (PCI) are relatively infrequent. The most common complications include discomfort and bleeding at the puncture site where the catheter was inserted. Major complications include death, MI, or stroke and other infrequent complications include transient ischemic attacks (minor myocardial injury), vascular complication and contrast induced nephropathy, transient ischemia, or minor myocardial injury (MMI), myocardial necrosis due to compromisation of threatened coronary circulation during balloon inflation. Cardiac Troponin I (cTnI) assays for the assessment of myocardial injury has been demonstrated for the diagnosis of MMI and long term prognosis after PCI. Delta Med Col J. Jul 2017 5(2): 94-98